Azimuthal stability of trichel pulses and cathode directed streamers - Bolotov, O.; Kadolin, B.; Mankovskyi, S.; Ostroushko, V.; Pashchenko, I.; Taran, G.; Zavada, L. (Вопросы атомной науки и техники, 2019)
The numerical simulations of negative corona discharge in Trichel pulse mode are carried out with the calculation of evolution of azimuthal perturbations. It is found the azimuthal instability with increment corresponding to avalanche development. This instability is suppressed at the nonlinear stage and does not lead to the process branching. The result is also applicable to the azimuthal instability of the cathode directed streamer, found earlier. The difference in their increments is followed from the difference in courses of the processess, which is discussed.